2011
DOI: 10.1504/ijcvr.2011.042271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of font size, italics, and colour count on web usability

Abstract: Web usability measures the ease of use of a website. This study attempts to find the effect of three factors – font size, italics, and colour count – on web usability. The study was performed using a set of tasks and developing a survey questionnaire. We performed the study using a set of human subjects, selected from the undergraduate students taking courses in psychology. The data computed from the tasks and survey questionnaire were statistically analysed to find if there was any effect of font size, italic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…phone ringing). The issues identified are consistent with work by Lee and Kozar [58] and Bhatia et al [59] who both suggest that legibility is a key aspect of usability.…”
Section: Discussionsupporting
confidence: 86%
“…phone ringing). The issues identified are consistent with work by Lee and Kozar [58] and Bhatia et al [59] who both suggest that legibility is a key aspect of usability.…”
Section: Discussionsupporting
confidence: 86%
“…Over time researchers agreed and countered one another's findings, although most prior research has demonstrated that font choice and features affect the participants' preferences [20][21][22]. Conversely, the authors of this study [23] contradict. Font choice has been observed to affect the reading speed in some studies [20,21], though some have not [22,[24][25][26].…”
Section: Analysis Of Difference Between Different Typeface Groupsmentioning
confidence: 46%
“…Font choice has been observed to affect the reading speed in some studies [20,21], though some have not [22,[24][25][26]. Prior research on the relationship between font size and reading speed is also divided, where's, some studies indicate that font size does affect reading speed [20,24], while others do not [23,25]. When comparing diverse typographic parameters, even Boyarski et al influential work revealed mixed findings [26].…”
Section: Analysis Of Difference Between Different Typeface Groupsmentioning
confidence: 99%
“…This effect is also found in (Beymer, Russell, and Orton 2005) research on the effect of line length on reading.On the other hand, Beymer et al research result however indicates that, although the small font is reducing the sweeping time. It is however increasing the fixation time compared to a larger font size.Based on (Bernard et al, 2002), (Bhatia, Samal, Rajan, and Kiviniemi, 2011), and (Ivory, and Hearst, 2002) researches, they indicated that font size at least 12 pt is the best suited for the web page. Table 2 below summarizes the studies that have been conducted on font size.…”
Section: Comparison Between Type Of Fontsmentioning
confidence: 99%